Investigating prejudice toward men perceived to be Muslim: cues of foreignness versus phenotype. (15th May 2013) - Brown, Lisa M.; Awad, Germine H.; Preas, Elizabeth J.; Allen, Valerie; Kenney, Jerry; Roberts, Stephanie; Lusk, L. Brooke
Abstract: Possible factors in prejudice toward Muslims and those perceived to be Muslims were investigated. We specifically investigated cues of foreignness that may communicate threat. Using a 2 (Complexion: dark vs. light) × 2 (Dress: Middle Eastern vs. Western) × 2 (Name: Allen vs. Mohammed) between‐subjects design, we expected cues of foreignness (dress and name) to have a greater impact on perceptions of targets than phenotype (complexion). Participants reviewed portraits of young men varying in the manipulated characteristics and gave their impressions. Generally, complexion did not affect perceptions, but portraits in Middle Eastern dress were rated less positively. There was a name by dress interaction in which Allen in Western dress was rated least negatively. Implications for future research are discussed.